2021
DOI: 10.3389/fendo.2021.751373
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Nomograms to Predict Blastulation Rate Following Cycles of In Vitro Fertilization in Patients With Tubal Factor Infertility, Polycystic Ovary Syndrome, or Endometriosis

Abstract: It is well known that the transfer of embryos at the blastocyst stage is superior to the transfer of embryos at the cleavage stage in many respects. However, the rate of blastocyst formation remains low in clinical practice. To reduce the possibility of wasting embryos and to accurately predict the possibility of blastocyst formation, we constructed a nomogram based on range of clinical characteristics to predict blastocyst formation rates in patients with different types of infertility. We divided patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(46 reference statements)
1
4
0
Order By: Relevance
“…outcomes(Hariton et al, 2017). It was shown that high-quality Day 3 embryos have more potential to develop into blastocysts(Yin et al, 2014), in the present study high-quality rate of Day 3 embryos extended culture to blastocyst stage corresponded to a high point; these results were similar to the previously predicted models(Dessolle et al, 2009;Jin et al, 2021).…”
supporting
confidence: 90%
See 3 more Smart Citations
“…outcomes(Hariton et al, 2017). It was shown that high-quality Day 3 embryos have more potential to develop into blastocysts(Yin et al, 2014), in the present study high-quality rate of Day 3 embryos extended culture to blastocyst stage corresponded to a high point; these results were similar to the previously predicted models(Dessolle et al, 2009;Jin et al, 2021).…”
supporting
confidence: 90%
“…Dessolle et al, 2009;Jin et al, 2021). The causation of the number of Day 3 embryos extended culture to blastocyst stage rather than the number of oocytes retrieved entered in the model, may be attributed to the fact that not all Day 3 embryos cohort were cultured to blastocyst stage and usually the best one or two embryos were transferred or vitri ed in the present study.The fertilization rate, cleavage rate, high-quality rate of Day 3 embryos extended culture to blastocyst stage were residual predictors of usable blastocyst formation on Day 5.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The discrimination calibration abilities of this model were evaluated by calculating receiver operating characteristic curves (ROC), area under the ROC curve (AUC), Harrell’s concordance index (C-index), and the calibration plots in the training and validation groups ( 14 ). The value of the C-index and AUC ranges from 0 to 1, with 0.5-0.7 indicating poor performance of this model, 0.7-0.8 demonstrating fair performance, and 0.8-0.9 suggesting good performance ( 22 ). R software (version 4.0.5) was used to construct the nomogram model and analyze the ROC, AUC, C-index, and calibration curve.…”
Section: Methodsmentioning
confidence: 98%